Collective Movement and Collective Information Acquisition With Signaling - Salahshour, Mohammad; Rouhani, Shahin (Frontiers in Physics, 2021)
We consider a population of mobile agents able to make noisy observations of the environment and communicate their observation by production and comprehension of signals. Individuals try to align their movement direction with their neighbors. Besides, they try to collectively find and travel towards an environmental direction. We show that, when the fraction of informed individuals is small, by increasing the noise in communication, similarly to the Vicsek model, the model shows a discontinuous order-disorder transition with strong finite-size effects. In contrast, for a large fraction of informed individuals, it is possible to go from the ordered phase to the disordered phase without passing any phase transition. The ordered phase is composed of two phases separated by a discontinuous transition. Informed collective motion, in which the population collectively infers the correct environmental direction, occurs for a high fraction of informed individuals. When the fraction of informed individuals is low, the misinformed collective motion, where the population fails to find the environmental direction, becomes stable as well. Besides, we show that an amount of noise in the production of signals is more detrimental for the inference capability of the population and increases temporal fluctuations, the density fluctuations, and the probability of group fragmentation, compared to the same amount of noise in the comprehension.